Physician Effectiveness in Interventions to Improve Cardiovascular Medication Adherence: A Systematic Review - Cutrona, Sarah L. (Springer-Verlag, 2010)
BACKGROUND: Medications for the prevention and treatment of cardiovascular disease save lives but adherence is often inadequate. The optimal role for physicians in improving adherence remains unclear. OBJECTIVE: Using existing evidence, we set the goal of evaluating the physician’s role in improving medication adherence. DESIGN: We conducted systematic searches of English-language peer-reviewed publications in MEDLINE and EMBASE from 1966 through 12/31/2008. SUBJECTS AND INTERVENTIONS: We selected randomized controlled trials of interventions to improve adherence to medications used for preventing or treating cardiovascular disease or diabetes. MAIN MEASURES: Articles were classified as either (1) physician “active”—a physician participated in designing or implementing the intervention; (2) physician “passive”—physicians treating intervention group patients received patient adherence information while physicians treating controls did not; or (3) physicians noninvolved. We also identified studies in which healthcare professionals helped deliver the intervention. We did a meta-analysis of the studies involving healthcare professionals to determine aggregate Cohen’s D effect sizes (ES). KEY RESULTS: We identified 6,550 articles; 168 were reviewed in full, 82 met inclusion criteria. The majority of all studies (88.9%) showed improved adherence. Physician noninvolved studies were more likely (35.0% of studies) to show a medium or large effect on adherence compared to physician-involved studies (31.3%). Among interventions requiring a healthcare professional, physician-noninvolved interventions were more effective (ES 0.47; 95% CI 0.38–0.56) than physician-involved interventions (ES 0.25; 95% CI 0.21–0.29; p < 0.001). Among physician-involved interventions, physician-passive interventions were marginally more effective (ES 0.29; 95% CI 0.22–0.36) than physician-active interventions (ES 0.23; 95% CI 0.17–0.28; p = 0.2). CONCLUSIONS: Adherence interventions utilizing non-physician healthcare professionals are effective in improving cardiovascular medication adherence, but further study is needed to identify the optimal role for physicians. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-010-1387-9) contains supplementary material, which is available to authorized users.